Blood Chimerism in Dizygotic Monochorionic Twins During 5 Years Observation. Issue 10 (11th May 2017) - Dziegiel, M. H.; Hansen, M. H.; Haedersdal, S.; Barrett, A. N.; Rieneck, K.; Main, K. M.; Hansen, A. T.; Clausen, F. B.
Abstract : Dizygotic monochorionic twin pregnancies can result in blood chimerism due to in utero twin‐to‐twin exchange of stem cells. In this case, we examined the proportion of allogeneic red blood cells by flow cytometry and the proportion of allogeneic nucleated cells by digital polymerase chain reaction at 7 months and again at 5 years. We found an increase in the proportion of allogeneic cells from 63% to 89% in one twin, and a similar increase in autologous cells in the other twin from 57% to 84%. A paradigm for stem cell therapy could be modeled on this case: induction of tolerance and chimerism by antenatal transfusion of donor stem cells. The procedure would hold the promise of transplantation and tolerance induction without myeloablative conditioning for inheritable benign hematological diseases such as sickle cell disease and thalassemia. Abstract : A substantial chimerism present at delivery and spontaneously increasing indicates that antenatal transfusion of stem cells could be a treatment for inheritable benign hematological diseases.